Z for Zachariah [videorecording (DVD)] - Robbie, Margot, 1990-; Pine, Chris, 1980-; Ejiofor, Chiwetel, 1977-; O'Brien, Robert C. (Grindstone, 2015)
Three young people find themselves caught up in a love triangle after a disaster has wiped out most of civilization.